Age‐dependent timing and routes demonstrate developmental plasticity in a long‐distance migratory bird. Issue 3 (9th December 2021) - Verhoeven, Mo A.; Loonstra, A. H. Jelle; McBride, Alice D.; Kaspersma, Wiebe; Hooijmeijer, Jos C. E. W.; Both, Christiaan; Senner, Nathan R.; Piersma, Theunis
Abstract: Longitudinal tracking studies have revealed consistent differences in the migration patterns of individuals from the same populations. The sources or processes causing this individual variation are largely unresolved. As a result, it is mostly unknown how much, how fast and when animals can adjust their migrations to changing environments. We studied the ontogeny of migration in a long‐distance migratory shorebird, the black‐tailed godwit Limosa limosa limosa, a species known to exhibit marked individuality in the migratory routines of adults. By observing how and when these individual differences arise, we aimed to elucidate whether individual differences in migratory behaviour are inherited or emerge as a result of developmental plasticity. We simultaneously tracked juvenile and adult godwits from the same breeding area on their south‐ and northward migrations. To determine how and when individual differences begin to arise, we related juvenile migration routes, timing and mortality rates to hatch date and hatch year. Then, we compared adult and juvenile migration patterns to identify potential age‐dependent differences. In juveniles, the timing of their first southward departure was related to hatch date. However, their subsequent migration routes, orientation, destination, migratory duration and likelihood of mortality were unrelated to the year or timing of migration, or their sex. Juveniles left the Netherlands after all tracked adults. They then flew non‐stop to West Africa more often and incurred higher mortality rates than adults. Some juveniles also took routes and visited stopover sites far outside the well‐documented adult migratory corridor. Such juveniles, however, were not more likely to die. We found that juveniles exhibited different migratory patterns than adults, but no evidence that these behaviours are under natural selection. We thus eliminate the possibility that the individual differences observed among adult godwits are present at hatch or during their first migration. This adds to the mounting evidence that animals possess the developmental plasticity to change their migration later in life in response to environmental conditions as those conditions are experienced. Abstract : The first southward and northward migrations of juvenile black‐tailed godwits are considerably different from those of adults. This demonstrates that godwits must develop their eventual routines over multiple years. Photo credit: Jan van de Kam.